The concerted impact of domestication and transposon insertions on methylation patterns between dogs and grey wolves. Issue 8 (18th January 2016) - Janowitz Koch, Ilana; Clark, Michelle M.; Thompson, Michael J.; Deere‐Machemer, Kerry A.; Wang, Jun; Duarte, Lionel; Gnanadesikan, Gitanjali E.; McCoy, Eskender L.; Rubbi, Liudmilla; Stahler, Daniel R.; Pellegrini, Matteo; Ostrander, Elaine A.; et al.
Abstract: The process of domestication can exert intense trait‐targeted selection on genes and regulatory regions. Specifically, rapid shifts in the structure and sequence of genomic regulatory elements could provide an explanation for the extensive, and sometimes extreme, variation in phenotypic traits observed in domesticated species. Here, we explored methylation differences from >24 000 cytosines distributed across the genomes of the domesticated dog ( Canis familiaris ) and the grey wolf ( Canis lupus ). PCA and model‐based cluster analyses identified two primary groups, domestic vs. wild canids. A scan for significantly differentially methylated sites (DMSs) revealed species‐specific patterns at 68 sites after correcting for cell heterogeneity, with weak yet significant hypermethylation typical of purebred dogs when compared to wolves (59% and 58%, P  < 0.05, respectively). Additionally, methylation patterns at eight genes significantly deviated from neutrality, with similar trends of hypermethylation in purebred dogs. The majority (>66%) of differentially methylated regions contained or were associated with repetitive elements, indicative of a genotype‐mediated trend. However, DMSs were also often linked to functionally relevant genes (e.g. neurotransmitters). Finally, we utilized known genealogical relationships among Yellowstone wolves to survey transmission stability of methylation marks, from which we found a substantial fraction that demonstrated high heritability (both H 2 and h 2  > 0.99). These analyses provide a unique epigenetic insight into the molecular consequences of recent selection and radiation of our most ancient domesticated companion, the dog. These findings suggest selection has acted on methylation patterns, providing a new genomic perspective on phenotypic diversification in domesticated species.